2011
DOI: 10.1590/s1808-86942011000600003
|View full text |Cite
|
Sign up to set email alerts
|

Tontura em idosos da comunidade: estudo de base populacional

Abstract: Dizziness is a common complaint among older adults. Aim To identify the prevalence of dizziness and its related factors in a sample of community-dwelling older adults. Methods A prospective population-based study with a representative sample of older adults aged 65 years and over. A multidimensional questionnaire and a battery of measures were used for assessing physical function. Results The prevalence of dizziness was 45%. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
2
9
0
5
Order By: Relevance
“…Literature points out that these problems are expected to be associated with the risk of falls, and this study reinforces findings (16)(17)19) that can determine serious consequences, including death.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Literature points out that these problems are expected to be associated with the risk of falls, and this study reinforces findings (16)(17)19) that can determine serious consequences, including death.…”
Section: Discussionsupporting
confidence: 86%
“…This research identified that auditory deficit is related to the high risk of falls. The study analyzed the prevalence of vertigo and associated factors in a group of elderly people and found that the sensation of falling was related to the auditory deficit and recurrent falls (19) . Moreover, it also mentioned that vestibular dysfunctions limit control and cause postural misalignment, which may explain how dizziness can be a trigger for falls.…”
Section: Discussionmentioning
confidence: 99%
“…Among the health problems, dizziness was mostly associated with the occurrence of falls. Bretan et al 29 also found an association between dizziness and the occurrence of falls among elderly attending an outpatient clinic in the city of Botucatu, São Paulo, as well as the cohort study by Moraes et al 30 , conducted with the population of elderly people in Cuiabá, Mato Grosso, in which dizziness was present among 51% of the individuals who reported falls in the past year.…”
Section: Discussionmentioning
confidence: 84%
“…The most common place where falls occur was the household of the elderly person (64%), followed by the streets (26%). Studies show that falls happen mostly in the bedroom and in the bathroom 49,30 , and that facilitating factors that stand out in the house are rugs, wet floor, changes in the position of furniture, little light and staircases 7 . Therefore, it is important to assess the household environment and the extrinsic factors that contribute with the occurrence of falls, as well as ways to prevent them, such as the use of non-slippery flooring material, adequate lighting, absence of rugs, support bars, and others 7,10 .…”
Section: Discussionmentioning
confidence: 99%
“…A grande variedade de causas e o significativo aumento de ocorrência com o envelhecimento (Hueb & Feliciano, 2012) são fatores que dificultam a análise dos dados relativos à tontura na população estudada, bem como, dos tipos de tontura verificados. Apesar de não haver diferença estatisticamente significante entre as tonturas rotatórias e não rotatórias verificadas no estudo, a literatura tende a apresentar resultados variáveis, com maiores prevalências de tonturas do tipo rotatória (Moraes et al, 2011) ou do tipo não-rotatória (Gazzola et al, 2006), assim como observado no presente estudo, com 71,4%, 60% e 50% entre os grupos Controle, Químico e Ruído, respectivamente, de presença de tonturas do tipo não rotatória.…”
Section: Discussionunclassified